Online Club Management System for UiTM Terengganu (On-ClubS) / Syarifah Husna Syd.Amra - Syd.Amra, Syarifah Husna (2017)
Nowadays, web-based system is implemented for numerous information processing and it is being used in every organization including educational institution. In universities, processing new club establishment proposals and club event proposals are a repetitive cycle of work for the Student Affairs Department (SAD) administration every semester. Currently, the proposal process is handled manually involving a bunch of paper usage and processing time consumption. Thus, this project provided the insight for the initiative to improve the way UiTM Terengganu’s SAD handles those proposals by incorporating an online system. The web-based system developed is called the Online Club Management System (ON-CLUBS) which accommodate the staff, lecturers and students for a more efficient task completion process. The development process followed the system development life cycle (SDLC) and extreme programming (XP) model was implemented. Evaluation by using questionnaire, showed a positive response from the respondents for the system’s interface design, usability, platform suitability, security, efficiency, and information quality. Analysis on the responses gave the highest mean of 4.05 (SD=0.41) for usability construct. Thus, it can be said that the system can give sufficient benefit to the users. Recommendations for future enhancement include improvement on information quality and additional functionality such as online club member registration.